Marine ecoregion and Deepwater Horizon oil spill affect recruitment and population structure of a salt marsh snail. Issue 12 (21st December 2016) - Pennings, Steven C.; Zengel, Scott; Oehrig, Jacob; Alber, Merryl; Bishop, T. Dale; Deis, Donald R.; Devlin, Donna; Hughes, A. Randall; Hutchens, John J.; Kiehn, Whitney M.; McFarlin, Caroline R.; Montague, Clay L.; et al.
Abstract: Marine species with planktonic larvae often have high spatial and temporal variation in recruitment that leads to subsequent variation in the ecology of benthic adults. Using a combination of published and unpublished data, we compared the population structure of the salt marsh snail, Littoraria irrorata, between the South Atlantic Bight and the Gulf Coast of the United States to infer geographic differences in recruitment and to test the hypothesis that the Deepwater Horizon oil spill led to widespread recruitment failure of L. irrorata in Louisiana in 2010. Size‐frequency distributions in both ecoregions were bimodal, with troughs in the distributions consistent with a transition from sub‐adults to adults at 13 mm in shell length as reported in the literature; however, adult snails reached larger sizes in the Gulf Coast. The ratio of sub‐adults to adults was 1.5–2 times greater in the South Atlantic Bight than the Gulf Coast, consistent with higher recruitment rates in the South Atlantic Bight. Higher recruitment rates in the South Atlantic Bight could contribute to higher snail densities and reduced adult growth in this region. The ratio of sub‐adults to adults in Louisiana was lower in 2011 than in previous years, and began to recover in 2012–2014, consistent with widespread recruitment failure in 2010, when large expanses of spilled oil were present in coastal waters. Our results reveal an important difference in the ecology of a key salt marsh invertebrate between the two ecoregions, and also suggest that the Deepwater Horizon oil spill may have caused widespread recruitment failure in this species and perhaps others with similar planktonic larval stages.